STRATEGI PEMASARAN PRODUK DIGITAL PRINTING PADA CV. FNB DIGITAL JAMBI - Yenni Yuniarti; Sarah Mauliana (DIGEST MARKETING, 2012)
CV. Digital FNB is one of the companies that involved in Digital Printing business. Based on survey in the middle of 2011-2012, there are 31 digital printing businesses in the city of Jambi. In order to examine the marketing stratey implemented, descriptive study has been conducted, uses interview, observation, and documentation as instruments. The strategy that observed in this study consist of marketing strategy including market segmentation, targeting, product strategy, pricing strategy, promotional strategy, and place/ location strategy, or more precisely the marketing mix. These strategies are examined through descriptive study. Briefly the result shows that CV.FNB Digital practiced the strategy as follows. Market segmentation is based on the demographic and geographic. The target market is company’s public and institutions, education, and events. Product strategy is practiced by the observed firms through product policy by determine the quality, product classification, product development with the addition of new products, determinant of the quality of the machine, and product design. Pricing strategy used basic pricing, competitor orientation, discounts, and market demand. Promotion strategy used advertising banner and brosur, public relation seminar/ event, personal selling, direct marketing internet/facebook, and Word of Mouth (WoM). Place strategy used direct distribution and determining the strategic location in the city centre.